2018
DOI: 10.1111/sjop.12498
|View full text |Cite
|
Sign up to set email alerts
|

Universal parental support for parents of adolescents: Who wants municipality‐based parental support and in what form?

Abstract: Parenting a child through adolescence can be a challenge for many parents; adolescents go through notable developmental, physical, and psychological changes that affect the relationships around them. Most parents find parental support during these years important. These young people's relationships with their parents are important to their mental health, but although parental support is universally available to parents of younger children, it is still scarce for parents of adolescents. The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Previous research has shown that Swedish parents prefer “easy‐to‐get” information, such as online or via a telephone help line as immediate support for parents searching for advice (Thorslund, Alfredsson & Axberg, 2018). Other research shows that self‐led information‐seeking is dependent on parent educational level (Alfredsson & Broberg, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that Swedish parents prefer “easy‐to‐get” information, such as online or via a telephone help line as immediate support for parents searching for advice (Thorslund, Alfredsson & Axberg, 2018). Other research shows that self‐led information‐seeking is dependent on parent educational level (Alfredsson & Broberg, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is important to consider that previous research recommends awareness of increased inequalities as an unwanted side-effect of universally offered parenting interventions through, among other things, a skewed distribution of socioeconomic variables among recruited parents [ 40 ]. Further, as there is evidence that some (effective) public health interventions, such as smoking cessation programs, might increase inequalities due to different response to the intervention based on socioeconomic differences [ 93 ], it can be argued that parenting programs carry this potential risk as well.…”
Section: Discussionmentioning
confidence: 99%
“…Parents in Sweden are seeking out parent training for various reasons: curiosity, specific problems that they need help to tackle, or following recommendations from friends [ 39 ]. Parents who perceive their own parenting capacity as low and believe their children have mental health or behavioural problems are more interested in receiving parenting support [ 40 ]. Further, it has been stated [ 40 ] that individual or group formats have the potential of reaching families with more difficulties, while lighter formats such as seminars reach parents with higher education, hence using only the latter delivery format might increase inequalities.…”
Section: Introductionmentioning
confidence: 99%